Teaching Concept Sentence Technique on Students’ Achievement in Writing Narrative - Meida Rabia Sihite; Wiki Tedi Rahmawati; Iskandar Zulkarnain (English Teaching and Linguistics Journal (ETLiJ), 2021)
The objective of this research was to investigate if Concept Sentence Technique significantly affected students’ achievement in writing narrative. This research was conducted by using experimental research design. The population was all students of grade X TKJ of PAB-10 Patumbak with the total number of students was 30 students. There were two parallel classes, namely X TKJ-1 and X TKJ-2. Each class consisted of 15 students. By employing cluster random sampling technique, X TKJ-1was selected as experimental group and X TKJ-2 was selected as control group. The experimental group was taught by applying Concept Sentence Technique, while the control group was taught by applying Conventional Technique. The instrument for collecting the data was writing test. The data were analyzed by using Mann Whitney U-test Formula. After the data had been calculated, it was found that the smaller U-observed value was 11.9. It was smaller than U-table value which was 75 at p=0.05 (11.9 < 64). It meant that the alternative hypothesis (Ha) was successfully accepted and Null Hypothesis (Ho) was successfully rejected. Based on the research finding, it was found that Concept Sentence Technique significantly affected students’ achievement in writing narrative.